The use of Adjective Phraseologisms in the Epic "Koblan" - Azamat Abdiev; Gulzhakhan Allambergenova (International Journal on Economics, Finance and Sustainable Development, 2021)
The article is devoted to the study of phraseologisms in the epic "Koblan", which is one of the folk oral traditions of the Karakalpak language. The authors of the article have studied the peculiarities of the use of phraseologisms in the language of the epic, the adjective meaningful phraseologisms among the parts of speech. In this regard, based on the work of well-known scholars and researchers, the phraseologisms were collected from the oral tradition of the people. The language of the epic “Koblan” of the Karakalpak folklore is rich in phraseologisms. They are used to create the image of the characters in the epic, to draw portraits, characters, and landscapes, to describe the character's behavior, psychology, mood, attitudes, perceptions, and used in the services of stylistic devices such as epithets, metaphors, irony, hyperbole, and litotes.